2004
DOI: 10.1212/wnl.62.2.212
|View full text |Cite
|
Sign up to set email alerts
|

Painful stimuli evoke itch in patients with chronic pruritus

Abstract: The chronic barrage of pruriceptive input may elicit central sensitization for itch so that nociceptive input no longer inhibits itch but on the contrary is perceived as itch. In contrast to the well-known A-fiber-mediated alloknesis and hyperknesis, this type of central sensitization appears to be elicited by C-nociceptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
168
2
11

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(190 citation statements)
references
References 35 publications
9
168
2
11
Order By: Relevance
“…62) This finding is consistent with the clinical feature of chronic pruritus such as atopic dermatitis that patients are often urged to keep scratching once they start it, suggesting that scratching does not only inhibit but also generate itch. on the other hand, pain sensitization causes a contrastive phenomenon.…”
Section: Itch Sensitizationsupporting
confidence: 79%
“…62) This finding is consistent with the clinical feature of chronic pruritus such as atopic dermatitis that patients are often urged to keep scratching once they start it, suggesting that scratching does not only inhibit but also generate itch. on the other hand, pain sensitization causes a contrastive phenomenon.…”
Section: Itch Sensitizationsupporting
confidence: 79%
“…It has been shown that itch can be evoked in patients with atopic dermatitis by mechanical, electrical, thermal, and low-pH stimuli that are normally painful (19). This finding is consistent with one of the well-known clinical features of patients with atopic dermatitis that they cannot stop scratching once they start it.…”
Section: Itch Sensitization In Atopic Dermatitissupporting
confidence: 79%
“…In certain pathological conditions, it may also modulate the modality of the sensation. It has been observed that in lesioned areas of atopic dermatitis patients, nociceptive stimuli such as bradykinin treatment or electrical stimuli are perceived as itching and not as pain [56,57] .…”
Section: Sensitization and Regulatory Mechanisms Of Itch And Painmentioning
confidence: 99%